Complex Language Analysis as One of the Methods in Teaching Czech as a Foreign Language - Květoslava Klímová; Martina Kurowski; Hana Svobodová (Charles University, 2022)
As the number of foreigners in the Czech Republic keeps rising, teachers are faced with the novel task of teaching Czech as a foreign language. Approaching this issue, the authors here discuss the method of 'complex language analysis', which supports the learning process by reconnecting abstract language expressions with the real world. Three functions are particular to this method: motivation, repetition, and practising of the curriculum, deepening the understanding of the new schoolwork.